ANALISIS PENGETAHUAN TEKNOLOGI PADA PENDEKATAN TPACK DI SEKOLAH DASAR - Uswatun Khasanah; Dian Kusmaharti; Wahyu Susiloningsih (Lembaga Pengembangan Kinerja Dosen, 2022)
The problem faced in this study is how the activity of the technological capabilities of teachers and students in the TPACK approach of elementary school. The purpose of this research is to analyze the technological capabilities of teachers and students in learning with the approach of TPACK. This type of research is qualitative approach. The subjects of this study are teachers and Students of elementary school. Data collection techniques use observations, interviews and documentation. The results of teacher technology capability activities such as learning using software in the form of: Blog, Microsoft Teams, Microsoft 365, Google Meet, Zoom, etc.), the ability to operate technology, learn technology, integrate technology, and use software conference is categorized enough. Teachers still don't meet all categories. While the results of student activities such as learning using software in the form of: Blog, Microsoft Teams, Microsoft 365, Google Meet, Zoom, etc.), the ability to operate technology, learn technology, integrate technology, and use conference software is categorized very well. Because students almost all meet the category.